Jingshin theoretical physics symposium in honor of prof Ta-You Wu (World Scientific, 1998)
Prof T-Y Wu is not only an eminent physicist with an encyclopedic knowledge, but also a motivational teacher and an influential policy maker in science and technology. The young Wu was inspired by Prof Y-T Yao, whose course on modern physics sparked an interest that burned during a long and productive career. Among Wu's achievements are 14 books and more than 120 papers covering subjects from atomic and molecular physics to plasmas and gases to atmospheric physics to relativity theory. Even at the age of 90 he remains active, publishing papers and lecturing on physics.Prof Wu feels grateful that he had the opportunity to educate a group of extremely talented students and, in particular, to discover T D Lee's remarkable talent. Although creative talent is no doubt a product of nature, it must also be nurtured. Prof Wu has played a crucial role for an entire generation of physicists in China and has won great respect from former students such as C N Yang, T D Lee, K Huang, and countless others. Prof Wu's love of physics and his dedication in teaching and research will always be remembered.